Comparisonal Analysis of Mechanical Properties on AISI 1095 Leaf Spring Steel With Steel Substitute Matrials Jis S45c and Jis Scm440 - Didin Zainudin; Setiyono S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Leaf springs are one of the components that function to soak the collision with the elastic properties of the material. where the leaf springs are made of steel materials such as AISI 1095 steel. In this study, a comparison of the mechanical properties of AISI 1095 leaf spring steels with S45C and SCM440 steels which are heat treated will be compared. Where the S45C material with a tempering temperature of 540°C obtains Yield Strength 555.6 MPa, and Ultimaate Strength 800.1 MPa, Hardness with an average of 69.3 HRA While at a temperature of 470°C obtains Yield Strength 561.3 MPa, and Ultimaate Strength 692.6 MPa, Hardness with an average of 71.5 HRA. For SCM440 having a tempering temperature of 540°C to get a Yield Strength of 829.8 MPa, and an Ultimaate Strength of 1053.7 MPa, Hardness with an average of 77.1 HRA While at a temperature of 470°C to obtain a Yield Strength of 846.4 MPa, and an Ultimaate Strength 1077.9 MPa, Hardness with an average of 70.7 HRA. From the results of this test, it is stated that the replacement material analyzed is close to the value of the SUP 10 steel spring.